Bio-medical wars in Canadian sport: issues in the prevention and detection of anabolic steroid use - Fogel, C. A. (Journal of Physical Education and Sport, 2013)
Despite efforts of league administrators to present a clean image of sport where athletic doping is under control, the use of steroids and other performance-enhancing drugs remains and is often not detected by doping control officers. Drawing on interviews with 59 male athletes eligible to be tested by doping control officers of the Canadian Centre for Ethics in Sports, as well as 22 administrators in sport, this paper highlights some of the ongoing issues in the current tests. Specifically, it examines how players are able to beat the test through numerous strategies such as playing the odds, timed drug cycling, using sustained low dosages, supplementing with epitestosterone, using masking agents, ingesting cleansers and diuretics, engaging in urine replacement, and using undetectable designer substances. This paper concludes with strategies to eradicate these issues.